New models of droplet deposition and entrainment for prediction of liquid film flow in vertical annuli. (25th February 2017) - Zhang, H.B.; Hewitt, G.F.
Highlights: A set of models of entrainment and deposition in annuli is developed. Good agreement between adiabatic annulus measurements and new methods is achieved. The new correlations are more suitable for dryout prediction of flows in annuli. Abstract: Droplet deposition and entrainment significantly affect dryout occurrences in annular two-phase flow. Currently, most of the correlations for droplet deposition and entrainment are derived from flows in tubes. However, the main challenge in thermal-hydraulic analyses of BWRs is the prediction of dryout occurrence in the rod bundle geometry of fuel assemblies. In the work reported here, the applicability of several tube-based droplet deposition and entrainment correlations to the annular geometry (effectively a "one-rod" bundle) is checked. It is found that the prediction values from all those correlations deviate from the experimental measurements. Therefore, a set of simple and easy-to-implement models for deposition and entrainment rates in annuli is developed based on the tube-based Hewitt-Govan correlations (Hewitt and Govan, 1990), with considering the liquid film flow characteristics in annuli and the geometry effect of the annulus. The present models are verified by comparison with experimental data for developing liquid films in adiabatic annuli. By using these models to predict dryout in heated annuli, we find that these new relationships have good capability in predicting dryout occurrence in annuli with uniform as well as non-uniform axial power distribution.